7x-6-3x=6x-5

Simple and best practice solution for 7x-6-3x=6x-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7x-6-3x=6x-5 equation:


Simplifying
7x + -6 + -3x = 6x + -5

Reorder the terms:
-6 + 7x + -3x = 6x + -5

Combine like terms: 7x + -3x = 4x
-6 + 4x = 6x + -5

Reorder the terms:
-6 + 4x = -5 + 6x

Solving
-6 + 4x = -5 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
-6 + 4x + -6x = -5 + 6x + -6x

Combine like terms: 4x + -6x = -2x
-6 + -2x = -5 + 6x + -6x

Combine like terms: 6x + -6x = 0
-6 + -2x = -5 + 0
-6 + -2x = -5

Add '6' to each side of the equation.
-6 + 6 + -2x = -5 + 6

Combine like terms: -6 + 6 = 0
0 + -2x = -5 + 6
-2x = -5 + 6

Combine like terms: -5 + 6 = 1
-2x = 1

Divide each side by '-2'.
x = -0.5

Simplifying
x = -0.5

See similar equations:

| 12+2b=60 | | -2p+8=5p-10 | | 60+50.4x=57.95x | | 3n+3=61 | | 8x+9=5x-29 | | 12(d+2)=3(d-8)+9d | | w-2w=4w+20 | | -13=-5a-(-12) | | 6x-3=-87 | | 5x+8=3y-6 | | 6.42-10*.392=2.5 | | 90+5x-9+3x+35=180 | | 9=T+6 | | -6x-5=10 | | 6-3x=5x-10+16 | | q-8=-14 | | ln(x^2-25)=0 | | 2y=78-5x | | Log(10)(x+3)-log(10)(x-3)=1 | | 10x+4x-3x=5-6x | | (x*2)-7=19 | | C=-4c | | 3(k-15)=-18 | | 5x=78-2y | | h+28=-3.7 | | 3a+25=10 | | 5/7=a/35 | | 9.5t+5=5+-4 | | 9x-3(3x-3)=9 | | 8y-9=-17 | | -12=-5-6*n+11 | | (3)-(-8)= |

Equations solver categories